Sustainability in the use of polyurethane and reuse of shavings (Research, Society and Development, 2020)
Polyurethane is one of the largest polymeric products in the plastic family. It is a material produced by a condensation reaction between polyols and isocyanates and can be used in a wide range of applications, which has triggered a marked growth in its use in recent years. It is considered a highly promising and versatile product due to its attractive morphology and wide range of desirable mechanical properties. The great commercial use leads to the generation of waste (shavings), and if not reused or disposed of correctly, this product causes environmental impacts. In this way, we want to evaluate the sustainability in relation to the use of this product and the possible reuse of the shavings. It was found that the main alternatives for shavings disposal are in landfills, incineration, recycling and recovery. The most sustainable option would be the reuse of shavings for the generation of other products. Processes were identified that created new products from waste and are advantageous because they reuse waste that did not owned a correct destination and for generating a source of income.